Anatomic and diagnostic considerations of facial mobility for understanding the effectiveness of facial massage: A pilot study. Issue 6 (25th May 2021) - Okuda, Itsuko; Yamada, Minoru; Yamada, Yoshitake; Yokoyama, Yoichi; Kampan, Natnicha; Akita, Keiichi; Jinzaki, Masahiro
Abstract: Background: The effectiveness of facial massage is often explained by the resulting increases in the blood and lymphatic flow. However, it is difficult to explain the lifting effect on the cheeks. The aim of this study was to analyze facial mobility to further current understanding of the effectiveness of facial massage. Materials and Methods: Two kinds of analytical methods were designed using a cadaveric head as well as advanced computed tomography (CT). The cadaveric face was divided into three sections, and three different colors of ink were injected into each section. It was kept in a supine position for 24 hours, and the ink distribution was observed. Upright and supine CT examinations were performed on six healthy adult volunteers. The images of both were superimposed by a three‐dimensional image analysis system, and changes in facial contours were analyzed. Results: The three colors of ink spread craniocaudally and were distributed differently from the gravitational vector. When both CT images were superimposed, two distinct lines were formed, which represented overlapping of the facial contours due to the two different CT images. These lines were found to correspond to the border of each color of the ink. Conclusion: Focusing on the mobility of the face, the soft tissue of the face had vertical mobility, and it was speculated that this mobility is involved in the effectiveness of facial massage. Our results could provide useful information for cosmetic treatment and contribute to the collection of scientific knowledge for anti‐aging medicine.